How do you solve

3/8x-1/3x+6=1/6x
asked Feb 2, 2012 in order of operations by anonymous

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:

To avoid this verification in future, please log in or register.

1 Answer

(3 / 8x) - (1 / (3x + 6)) = 1 / (6x)

Note that x cannot be 0 or -2, or we will have zero in the denominator of some of the terms.

[3(3x + 6) - (1)(8x)] / [(8x)(3x + 6)] = 1 / 6x
[9x + 18 - 8x] / [(24x)(x + 2)] = 1 / 6x
[x + 18] / [(24x)(x + 2)] = [4(x + 2)] / [(24x)(x + 2)]
x + 18 = 4(x + 2)
x + 18 = 4x + 8
4x - x = 18 - 8
3x = 10
x = 10 / 3
answered Feb 3, 2012 by anonymous

Related questions

1 answer
asked Nov 15, 2012 in order of operations by anonymous | 114 views
0 answers
0 answers
asked Sep 7, 2013 in Algebra 2 Answers by leslie Esling | 32 views
1 answer
asked May 5, 2013 in Algebra 1 Answers by anonymous | 51 views
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
76,951 questions
80,417 answers
1,582 comments
58,203 users